Variables Influencing the Potency of Community Based Coffee Agro-Tourism in Mount Galunggung, Tasikmalaya, Indonesia - Nurhana Jafaruddin; Trisna Insan Noor; Tuti Karyani (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Tourist attraction which located in the area of Mount Galunggung, Tasikmalaya Regency offers a variety of tourist destinations. The Mount Galunggung tourismarea is currently adding some tourist destinations, such as the development of coffee agro-tourism which involves the community, namely coffee farmers. However, the potential for coffee tourism still requires good planning and designing. The involvement of all stakeholders to support the development of coffee agro-tourism is expected to make coffee agro-tourism sustainable. The aims of this study were to analyze the factors which affect the development of coffee agro-tourism and to design a model for developing community-based coffee agro-tourism. The research design mixed method of census and Partial Least Square. The number of respondents was 142 that consisted of the community involved in the development of agro-tourism in Sukaratu District. The results of this study showed that the coffee plantation supported the existence of coffee agro-tourism in Galunggung tourism area. The characteristics of variable, agro-tourism resources institutional support and the potential of agro-tourism affected community-based agro-tourism. The model of community-based coffee agro-tourism development in Mount Galunggung tourism area is implemented by maximizing the input of community characteristics agro-tourism institutional support, and agro-tourism resources, especially the variable of agro-tourism potential so it can produce output for developing community-based agro-tourism potential. This output later will affect outcomes such as the enhancement income of farmers and local communities, the enhancement of coffee productivity, absorption of local labor, socio-cultural preservation, and the established cooperation between stakeholders.